KAJIAN PENGELOLAAN USAHATANI KELAPA DI DESA TOLOMBUKAN KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - Eyverson Ruauw; Jenny Baroleh; Devison Powa (Sam Ratulangi University, 2011)
This study aims to assess the management of coconut farms in village of Tolombukan district of Pasanmainly include land area, production, revenue, and marketing. The results could be input materials andinformation for farmers in increasing production and income of coconut farmers in of Tolombukan districtPasan.The research was carried on in the of Tolombukan district of Pasan which lasted from June 2010 untilAugust 2010. Data taken in this study are primary data that was obtained through interviews to farmersbased on a list of questions and secondary data obtained from agencies - agencies. Sampling method usedin this study is simple random sampling method with a sample size of 20 farmer respondents. Data is presentedin tables and is explained descriptively. The data are mainly in the form of costs, income, and revenue.Results showed that coconut farmers harvest pass once in 3 months so that in one year there are 4times the harvest with an average area of 1.59 ha. The other results of thisr studies are outlined below.The results of the average oil production in the village of Tolombukan district of Pasan of 2375.9 kg ofcopra per year with an average income of Rp4.891.948, 78 per year. In addition to plant coconut, farmersalso planted cloves between the coconut that provide an income of Rp11.734.695, 84 per two years orRp5.867.000 per year. The product of copra and cloves sold at traders in the village Tolombukan own.